WORK MANAGEMENT AND CONTINUING EDUCATION TO STRENGTHEN THE HEALTHCARE NETWORK (Editora Impacto Científico, 2025)
Strengthening the Health Care Network (RAS) within the Brazilian Unified Health System (SUS) depends on the articulation between work management and continuing education, aiming to guarantee comprehensive, equitable, and effective care. This study aimed to analyze how these strategies contribute to qualifying the workforce and improving health services, considering legal guidelines, national policies, and scientific evidence. This is a qualitative, descriptive, and exploratory research, based on bibliographic and documentary review. Scientific articles, books, technical reports, legislation, ordinances, and institutional documents published between 2017 and 2024 were analyzed, using descriptors such as work management, continuing education, human resources in health, and care networks. The results indicate that the fragmentation of work, professional turnover, precarious employment relationships, and insufficient planning compromise the effectiveness of the RAS, while collaborative practices, structured continuing education programs, and team integration contribute to improvements in the quality of care. The discussion highlights that work management strengthens coordination, communication, and safety of care, and that continuing education, by promoting continuous and reflective processes, develops critical and interprofessional skills. It is concluded that structured work management policies, associated with continuing education, are fundamental to consolidating the Health Care Network, strengthening the performance of professionals, and guaranteeing an efficient, democratic SUS capable of meeting the real needs of the Brazilian population, recognizing the worker as the protagonist of care practices.DOI: https://doi.org/10.56238/edimpacto2025.091-026